Metatranscriptomics of Nasopharyngeal Microbiota and Host Distinguish between Pneumonia and Health - Nannapaneni, Priyanka; Sundh, John; Prast-Nielsen, Stefanie; Rhedin, Samuel; Örtqvist, Åke; Naucler, Pontus; Henriques-Normark, Birgitta (American journal of respiratory and critical care medicine, 2022)
In order to map the expression of the nasopharyngeal microbiota and associated host responses in 20 healthy children and 20 children with CAP, we developed a novel metatranscriptomic pipeline with ultrasensitive sequencing of nasopharyngeal aspirates (https://doi.org/10.6084/m9.figshare.20452026.v2) (6). A control subject was chosen who was matched for age and calendar time for every child with CAP. Only one case and no control patients got antibiotics prior to sampling. Using the lllumina Novaseq 6000S1 deep sequencing system, which has two lanes with 2 · 150 bp read lengths and an estimated output of roughly 3 billion reads, DNA and RNA were concurrently extracted from the aspirates. A sample of the metatranscriptomic sequencing produced 15-60 million reads, of which 50-75 percent were from humans, 25-40% from bacteria, and less than 1% from viruses.